Communication Competency of School Leaders: A Systematic Review on the Impact on Effective STEM Teaching Professional Development Strategies - Jaafar, Rozaimi; Wan Mahmud, Wan Marfazila; P. Vilbar, Aurelio; Mohammad, Karimi (Semarak International Journal of STEM Education, 2024)
Communication competency among school leaders is crucial for enhancing educational outcomes, particularly in STEM education. This systematic review aims to synthesize existing research on the interplay between school leaders' communication competencies and STEM professional development outcomes, addressing the gap in understanding how these skills impact the effectiveness of STEM teaching strategies. The study's objectives are to identify key communication competencies of school leaders influential in STEM professional development, analyze their impact on the effectiveness of professional development strategies, and provide recommendations for enhancing STEM teaching through improved communication practices. A systematic literature review was conducted using Scopus and ERIC databases, focusing on studies published between 2014 and 2024. From 247 initially identified papers,21 articles were selected for final analysis based on predefined criteria. The analysis revealed three main themes: (1) Communication competency of school leaders is crucial for effective teaching and leadership; (2) STEM and professional development in education require multifaceted approaches, including cultural competence and collaborative problem-solving; (3) Digitalization and technology integration present both challenges and opportunities for school leaders in enhancing STEM education.